2017
DOI: 10.1007/s11682-017-9734-7
|View full text |Cite
|
Sign up to set email alerts
|

Does ventrolateral prefrontal cortex help in searching for the lost key? Evidence from an fNIRS study

Abstract: The Key Search Task (KST) is a neuropsychological test that requires strategies for searching a lost key in an imaginary field. This request may involve different cognitive processes as mental imagery and navigation planning. This study was aimed at investigating, by a twenty-channel functional near-infrared spectroscopy (fNIRS) system, the hemodynamic response (i.e., oxygenated-hemoglobin (OHb) and deoxygenated-hemoglobin (HHb) changes) of the prefrontal cortex in navigation planning. A right ventrolateral pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 59 publications
0
10
0
1
Order By: Relevance
“…The Key Search Task (Wilson et al, 1996) is an easy-toadminister and ecological test. It is one of the subtests of the 'Behavioural Assessment of the Dysexecutive Syndrome' (BADS: Wilson et al, 1996), and it has been recently adopted to assess travel planning (Bocchi et al, 2017(Bocchi et al, , 2019(Bocchi et al, , 2020Carrieri et al, 2018). It consists of an A4-sized piece of paper with the drawing of a 10 × 10 cm empty black square in the middle and a small black dot placed 5 cm below the centre of the base of the square (see Fig.…”
Section: The Kstmentioning
confidence: 99%
“…The Key Search Task (Wilson et al, 1996) is an easy-toadminister and ecological test. It is one of the subtests of the 'Behavioural Assessment of the Dysexecutive Syndrome' (BADS: Wilson et al, 1996), and it has been recently adopted to assess travel planning (Bocchi et al, 2017(Bocchi et al, , 2019(Bocchi et al, , 2020Carrieri et al, 2018). It consists of an A4-sized piece of paper with the drawing of a 10 × 10 cm empty black square in the middle and a small black dot placed 5 cm below the centre of the base of the square (see Fig.…”
Section: The Kstmentioning
confidence: 99%
“…At date, TP and VP have been considered two aspects of the same planning, sub-served by the same neurocognitive processes. Indeed, both of them may require the correct functioning of PFC (Martinet et al, 2011;Carrieri et al, 2018;Choi et al, 2018) to put together the right sequence of actions to reach a goal; however, TP could be considered a specific planning that shares with VP common processes but also differences. Indeed, Patient 2 who showed a deficit of TP but intact capabilities of VP did not show any lesion of PFC, suggesting that TP involves a network that mostly relies on other brain areas.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggested the existence of a specific planning ability devoted to solving navigational tasks (Basso et al, 2006;Cazzato et al, 2010;Martinet et al, 2011;Boccia et al, 2014a;Schacter et al, 2017). This ability has been called in several ways: visuospatial planning (VP; Basso et al, 2006;Cazzato et al, 2010), spatial navigational planning (Martinet et al, 2011;Schacter et al, 2017;Carrieri et al, 2018: Bocchi et al, 2017 or, even, travel planning (TP; Bocchi et al, 2019) that is the term we will adopt thereafter. Martinet et al (2011) defined TP as the mental evaluation of alternative action-sequences to infer optimal trajectories for reaching a goal, suggesting the dynamic nature of this kind of planning.…”
Section: Introductionmentioning
confidence: 99%
“…VLPFC is involved in integration of multisensory stimuli, processing visual‐object signals, spatial navigation and associating the results from these processes to motor responses and/or action control . In addition, VLPFC is also a part of the ventral attentional network responsible for reorienting attention in a bottom‐up manner when salient stimuli occur in the external environment .…”
Section: Discussionmentioning
confidence: 99%